Economics Education Subject Role in World - Iqbal Shaukat (Edunesia Journal, 2025)
Economation is very important for every nation.in the case of economic education we  can get the good status in the society. Economics is the back bone of every country and society.Economics system provide the way how to get the goal of development.With the help of economics we can get the consumer price index.Economic data provide information regarding the national income and percapita income.The benefit of economic study we can prove more beneficial for the society.Economic education provide the way how the all sectors can be developed.Economics data provide the information regarding the growth and development of nation. Key words: Economics, Devlopment.Growth